2019
DOI: 10.1038/s41598-019-47984-x
|View full text |Cite
|
Sign up to set email alerts
|

Field cancerization therapy with ingenol mebutate contributes to restoring skin-metabolism to normal-state in patients with actinic keratosis: a metabolomic analysis

Abstract: Actinic keratosis (AK) is a skin premalignant lesion, which progresses into squamous cell carcinoma (SCC) if left untreated. Ingenol mebutate gel is approved for local treatment of non-hyperkeratotic, non-hypertrophic AK; it also has the potential to act as a field cancerization therapy to prevent the progression of AK to SCC. To gain better insights into the mechanisms of ingenol mebutate beyond the mere clinical assessment, we investigated, for the first time, the metabolome of skin tissues from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The imbalance of GSH metabolism may be associated with major alterations of the redox state of the pathological tissue that could increase the requirement of antioxidant molecules, such as GSH, and it is a metabolomics signature of sun-exposed skin tissues [ 28 ]. This suggests an increase of skin metabolism both in SCC and in AK lesions of all grades, in line with our previous findings [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The imbalance of GSH metabolism may be associated with major alterations of the redox state of the pathological tissue that could increase the requirement of antioxidant molecules, such as GSH, and it is a metabolomics signature of sun-exposed skin tissues [ 28 ]. This suggests an increase of skin metabolism both in SCC and in AK lesions of all grades, in line with our previous findings [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Metabolic profiling was already applied to the study of cancer biology [ 15 , 16 , 17 , 18 ], also with the aim of identifying potential predictive disease biomarkers. A recent study already identified potential biomarkers of AK through integrated metabolomics and histopathological analysis, with the aim of investigating the effects of the field cancerization treatment [ 19 ]. However, metabolomics has been scantly applied to skin cancers and the association between AK lesions and SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Asc is known to counteract the oxidative stress 22 and represents an enzymatic cofactor of many biological processes. Moreover, in the skin, Asc may also influence morphology and differentiation of keratinocytes, as well as gene expression 23 . The increase of Asc in skin samples and the simultaneous decrease in sera shown in our study is in line with the results of a previous study and reinforces the evidence of a strong gradient of ascorbate from the blood to the epidermis as a possible compensatory mechanism to oxidative stress 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic profiles of skin and serum were obtained using a Bruker Avance III HD 600 MHz spectrometer 23 , 48 , 49 .…”
Section: Methodsmentioning
confidence: 99%
“…However, it was withdrawn from the EU in 2020, due to the observed development of skin cancer in ∼6% of patients using Picato ® . [14][15][16][17][18][19] Several studies regarding the isolation, synthesis, and anticancer 1 effects of diterpenoids from Euphorbia species have been published. These diterpenoids were reported to have antiproliferative, 20 cytotoxic, 21 antimicrobial, 22 and antipyretic-analgesic activities.…”
Section: Introductionmentioning
confidence: 99%